Answer:
Multiply 2x + 3y = −1 by 5. Multiply 3x − 5y = 10 by 3. Add the resulting equations together.
Explanation:
To eliminate the y-term. we must multiply both equations by values that make the coefficients of y opposite in sign.
2x + 3y = -1 (1)
3x - 5y = 10 (2)
The easiest way to do this is to multiply Equation (1) by 5
and Equation (2) by 3.
5 × [2x + 3y = -1]
3 × [3x - 5y = 10]
Then, add the two equations.
10x + 15y = -5
9x - 15y = 30
19x = 25
Conclusion: Multiply 2x + 3y = −1 by 5. Multiply 3x − 5y = 10 by 3. Add the resulting equations together.